Towards a theology of development in the Uniting Reformed Church in Southern Africa (URCSA): Embodying Article 4 of the Belhar Confession - Beukes, Jacques Walter (Missionalia, 2016)
The Belhar Confession gained shape following the social injustices that resulted from the policy of apartheid. Whilst the former mission church's role during the apartheid regime was that of resistance, its role in a post-apartheid South African context was supposed to change to reconstruction and assistance. Given the current socio-economic situation and injustices, the Belhar Confession is now more than ever relevant and should therefore be the basis and motivation for the church to serve and be involved in the fight against poverty in South Africa. The church is therefore challenged to not solely depend on welfare projects in their role as poverty combaters but to move beyond a charity mode towards a mode of development.